2011
DOI: 10.1089/cap.2010.0131
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine Use for the Adjunctive Treatment of Adolescents with Anorexia Nervosa

Abstract: Objective: To examine assessment and treatment profiles of adolescent patients with anorexia nervosa and eating disorder not otherwise specified who received olanzapine as compared with an untreated matched sample. Method: A retrospective, matched-groups comparison study was completed. Medical files of 86 female patients treated in the eating disorder program at the Children's Hospital of Eastern Ontario were examined. Patients treated with olanzapine were initially identified through chart review and then mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 26 publications
(24 reference statements)
2
38
1
Order By: Relevance
“…There is no evidence to suggest that pharmacotherapy in AN should be first line, but it may play a role in individual patients resistant to treatment or with premorbid psychiatric conditions. 107,[128][129][130] In BN, several RCTs in adults have found that antidepressants are effective in decreasing binge eating and purging symptoms. Specifically, fluoxetine has a strong evidence base and is approved by the Food and Drug Administration for use in adults with BN; thus far there is some evidence that the effects are similar in adolescents.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…There is no evidence to suggest that pharmacotherapy in AN should be first line, but it may play a role in individual patients resistant to treatment or with premorbid psychiatric conditions. 107,[128][129][130] In BN, several RCTs in adults have found that antidepressants are effective in decreasing binge eating and purging symptoms. Specifically, fluoxetine has a strong evidence base and is approved by the Food and Drug Administration for use in adults with BN; thus far there is some evidence that the effects are similar in adolescents.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…A recent work by Norris et al (2011) tried to retrospectively assess baseline characteristics in drug-treated AN patients compared with untreated ones. The authors concluded that despite their best attempt, they could not match the two groups for baseline characteristics.…”
Section: Discussion and Hypothesismentioning
confidence: 99%
“…Two (Kafantaris 2011;Norris 2011) showed no greater benefit of olanzapine over placebo. Similarly, a randomised trial of risperidone v. placebo found no effect on eating disorder rating scales or weight (Hagman 2011).…”
Section: Treatment Of Anorexia Nervosamentioning
confidence: 90%